The Economic Impact Of Job Hopping: A Scoping Review Of Labor Mobility - Fahrizal (Yayasan Cerdas Pedia Indonesia, 2026)
This systematic literature review investigates the evolution of job-hopping behavior within the global labor market during the transformative period of 2015 to 2025. Following PRISMA-ScR guidelines and using Scopus with Watase software, 18 high-quality studies were synthesized to identify multilevel determinants and economic consequences. Findings reveal that mobility is no longer merely an individual psychological choice but a rational response to structural market disequilibrium, wage inflation, and technological shifts. While interorganizational moves can enhance functional diversity and long-term employability, they simultaneously impose significant friction costs on firms through recruitment expenses and productivity losses. Geographically, emerging economies like Vietnam and India exhibit distinct mobility drivers compared to mature markets. The study concludes that optimizing talent allocation requires integrated policy interventions, including improved labor market information and strategic human capital management. These results provide frameworks for policymakers and managers to balance market flexibility with organizational stability in increasingly volatile global labor market landscapes.